An implicit solution method for digital construction of temperature fields in concrete structures based on point temperature measurements - Zhu, Zhenyang; Liu, Yi; Zhang, Lei (Engineering computations, 2024)
PurposeAt present, using the finite element method is difficult to efficiently and accurately construct the temperature field of mass concrete based on temperature measurement points. Thus, there is a need to propose a method for improvement.Design/methodology/approachThis study developed an implicit finite element method that digitally constructs the temperature field of mass concrete based on temperature measurement data. That is, in the proposed method of this paper, the temperature of the measuring point is also one of the boundary conditions, which real-time corrects the calculation error.FindingsIn this method, during the digital construction of the temperature field, the computed temperature approaches the actual measured value at the point of measurement with increasing iteration steps. Using this method and sufficient temperature measurement data, the errors in calculation conditions (such as the boundary conditions, the initial casting temperature and material parameters) can be automatically corrected during the iterative computation process.Originality/valueThis new method can improve calculation accuracy and allows the digitally constructed temperature field to converge to its true value with sufficient measurement data.